Dual signaling cascade regulating gut-lung axis in Interleukin-6/Interleukin-17 for NSCLC immuno pathogenesis - Khilwani, Riya; Singh, Shailza (Frontiers in Immunology, 2025)
Non-small cell lung cancer is the leading cause of death globally, affecting both men and women. Emerging evidence has highlighted the apparent role of gut microbiota in reshaping the lung microbial community. Notably, imbalances in the gut microbiome disrupt lung physiology, which increases an individual’s susceptibility to lung diseases. The homing of gut residents to pulmonary sites prompts tumorigenic processes by altering microbial synergism that metabolically reprograms immune effectors to complement tumor growth. Nevertheless, the additive effect of microbiomes induces immune-responsive mechanisms that excessively induce IL-6 and IL-17 at the inflamed site. Consequently, perturbations in cytokine pool boost inflammatory responses toward a pro-tumor effect, implying cytokine duality and the role of these interleukins in regulating gut-lung crosstalk. Inflammation is a natural host defense mechanism activated against foreign stimulants to mount an immune response. At later stages, the inductive effect of IL-6/17 triggers inflammasome assembly where their accelerated response induces lung epithelial damage, leading to cellular transformation. This implies that the unexplored interconnections between microbiomes and interleukin biology influence immune dynamics that regulate the processes of neoplastic transformation. Here, in this comprehensive review, we comment on the gut-lung crosstalk along with the role of resident microbes in generating immunological responses. Besides, we discuss the IL-6/17-mediated activation of the inflammasome in attuning tumoral immunity. These dictate the potential of microbiotal lifeforms in generating inflammatory responses, which can therefore serve as potential diagnostic markers in NSCLC.